Hoveyda–Grubbs catalysts with an N→Ru coordinate bond in a six-membered ring. Synthesis of stable, industrially scalable, highly efficient ruthenium metathesis catalysts and 2-vinylbenzylamine ligands as their precursors - Polyanskii, Kirill B.; Alekseeva, Kseniia A.; Raspertov, Pavel V.; Kumandin, Pavel A.; Nikitina, Eugeniya V.; Gurbanov, Atash V.; Zubkov, Fedor Ivanovich (Beilstein Journal of Organic Chemistry, 2019)
A novel and efficient approach to the synthesis of 2-vinylbenzylamines is reported. This involves obtaining 2-vinylbenzylamine ligands from tetrahydroisoquinoline by alkylation and reduction followed by the Hofmann cleavage. The resultant 2-vinylbenzylamines allowed us to obtain new Hoveyda–Grubbs catalysts, which were thoroughly characterised by NMR, ESIMS, and X-ray crystallography. The utility of this chemistry is further demonstrated by the tests of the novel catalysts (up to 10−2 mol %) in different metathesis reactions such as cross metathesis (CM), ring-closing metathesis (RCM) and ring-opening cross metathesis (ROCM).
Keywords: CM; cross metathesis; Hoveyda–Grubbs catalyst; olefin metathesis; RCM; ring-closing metathesis; ring-opening cross metathesis; ROCM; ruthenium metathesis catalyst; styrene; 2-vinylbenzylamine

(untitled) - Yu, M.; Lou, S.; Gonzalez-Bobes, F. (Org. Process Res. Dev., 2018)

(untitled) - Ogba, O. M.; Warner, N. C.; O’Leary, D. J.; Grubbs, R. H. (Chem. Soc. Rev., 2018)

(untitled) - Chen, Y.; Abdellatif, M. M.; Nomura, K. (Tetrahedron, 2018)

(untitled) - Mukherjee, N.; Planer, S.; Grela, K. (Org. Chem. Front., 2018)

(untitled) - Lecourt, C.; Dhambri, S.; Allievi, L.; Sanogo, Y.; Zeghbib, N.; Ben Othman, R.; Lannou, M.-I.; Sorin, G.; Ardisson, J. (Nat. Prod. Rep., 2018)

(untitled) - Biffis, A.; Centomo, P.; Del Zotto, A.; Zecca, M. (Chem. Rev., 2018)

(untitled) - Montgomery, T. P.; Johns, A. M.; Grubbs, R. H. (Catalysts, 2017)

(untitled) - Hughes, D.; Wheeler, P.; Ene, D. (Org. Process Res. Dev., 2017)

(untitled) - Sinclair, F.; Alkattan, M.; Prunet, J.; Shaver, M. P. (Polym. Chem., 2017)

(untitled) - Montgomery, T. P.; Ahmed, T. S.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2017)

(untitled) - Paradiso, V.; Costabile, C.; Grisi, F. (Molecules, 2016)

(untitled) - Higman, C. S.; Lummiss, J. A. M.; Fogg, D. E. (Angew. Chem., Int. Ed., 2016)

Handbook of Metathesis - Grubbs, R. H.; Wenzel, A. G.; O’Leary, D. J.; Khosravi, E. (Wiley-VCH, 2015)

Olefin Metathesis - van Lierop, B. J.; Lummiss, J. A. M.; Fogg, D. E. (Ring-Closing Metathesis, 2014)

(untitled) - Scholl, M.; Trnka, T. M.; Morgan, J. P.; Grubbs, R. H. (Tetrahedron Lett., 1999)

(untitled) - Scholl, M.; Ding, S.; Lee, C. W.; Grubbs, R. H. (Org. Lett., 1999)

(untitled) - Fürstner, A.; Ackermann, L.; Gabor, B.; Goddard, R.; Lehmann, C. W.; Mynott, R.; Stelzer, F.; Thiel, O. R. (Chem. – Eur. J., 2001)

(untitled) - Michrowska, A.; Bujok, R.; Harutyunyan, S.; Sashuk, V.; Dolgonos, G.; Grela, K. (J. Am. Chem. Soc., 2004)

(untitled) - Barbasiewicz, M.; Bieniek, M.; Michrowska, A.; Szadkowska, A.; Makal, A.; Woźniak, K.; Grela, K. (Adv. Synth. Catal., 2007)

(untitled) - Kos, P.; Savka, R.; Plenio, H. (Adv. Synth. Catal., 2013)

(untitled) - Engle, K. M.; Lu, G.; Luo, S.-X.; Henling, L. M.; Takase, M. K.; Liu, P.; Houk, K. N.; Grubbs, R. H. (J. Am. Chem. Soc., 2015)

(untitled) - Duan, Y.; Wang, T.; Xie, Q.; Yu, X.; Guo, W.; Wang, J.; Liu, G. (Dalton Trans., 2016)

(untitled) - Occhipinti, G.; Bjørsvik, H.-R.; Törnroos, W. K.; Jensen, V. R. (Organometallics, 2007)

(untitled) - Tzur, E.; Szadkowska, A.; Ben-Asuly, A.; Makal, A.; Goldberg, I.; Woźniak, K.; Grela, K.; Lemcoff, N. G. (Chem. – Eur. J., 2010)

CN Patent - Zannan Science and Technology (Shanghai) Co., Ltd.; Zheng-Yun, Z. (Metal complex ligand, metal complex, preparation method and use of metal complex, polymers and preparation method and use of polymers, 2008)

WO Patent - Francis Walter Cornelius Verpoort; Xia, L. (Group 8 transition metal catalysts and method for making same and process for use of same in olefin disproportionation reactions, 2016)

WO Patent - Zannan Scitech Co., Ltd.; Zhan, J. Z.-Y. (Highly active metathesis catalysts selective for ROMP and RCM reactions, 2009)

WO Patent - PJSC Rosneft Oil Co.; Polyanskii, K. B.; Afanas'ev, V. V.; Bespalova, N. B. (Dicyclopentadiene metathesis polymerization catalyst in the form of a ruthenium complex and method for producing same, 2014)

RU Patent - PJSC Rosneft Oil Co.; Polyanskii, K. B.; Afanasev, V. V.; Zemtsov, D. B.; Panov, D. M.; Bespalova, N. B. (Method of producing catalyst for metathesis polymerisation of dicyclopentadiene, 2015)

RU Patent - PJSC Rosneft Oil Co.; Polyanskii, K. B.; Afanas'ev, V. V.; Zemtsov, D. B.; Panov, D. M.; Bespalova, N. B. (Catalyst of metathesis polymerisation of dicyclopentadiene in form of ruthenium complex and method of obtaining thereof, 2014)

Olefin metathesis and metathesis polymerization - Ivin, K. J.; Mol, J. C. (Academic Press, 1997)

(untitled) - Shcheglova, N. M.; Kolesnik, V. D.; Ashirov, R. V.; Krasnokutskaya, E. A. (Russ. Chem. Bull., 2016)

(untitled) - Kiselev, S. A.; Lenev, D. A.; Lyapkov, A. A.; Semakin, S. V.; Bozhenkova, G.; Verpoort, F.; Ashirov, R. V. (RSC Adv., 2016)

(untitled) - Pump, E.; Leitgeb, A.; Kozłowska, A.; Torvisco, A.; Falivene, L.; Cavallo, L.; Grela, K.; Slugovc, C. (Organometallics, 2015)

(untitled) - Shcheglova, N. M.; Kolesnik, V. D.; Ashirov, R. V.; Krasnokutskaya, E. A. (Russ. J. Org. Chem., 2015)

(untitled) - Grudzień, K.; Żukowska, K.; Malińska, M.; Woźniak, K.; Barbasiewicz, M. (Chem. – Eur. J., 2014)

(untitled) - Ashirov, R. V.; Zemlyakov, D. I.; Lyapkov, A. A.; Kiselev, S. A. (Kinet. Catal., 2013)

(untitled) - Szadkowska, A.; Gstrein, X.; Burtscher, D.; Jarzembska, K.; Woźniak, K.; Slugovc, C.; Grela, K. (Organometallics, 2010)

(untitled) - Rheiner, A., Jr; Brossi, A. (Helv. Chim. Acta, 1962)

(untitled) - Ito, Y.; Nakatsuka, M.; Saegusa, T. (J. Am. Chem. Soc., 1982)

(untitled) - Suzuki, T.; Takamoto, M.; Okamoto, T.; Takayama, H. (Chem. Pharm. Bull., 1986)

(untitled) - Kafka, S.; Trška, P.; Kytner, J.; Taufmann, P.; Ferles, M. (Collect. Czech. Chem. Commun., 1987)

(untitled) - Padwa, A.; Dent, W. (J. Org. Chem., 1987)

(untitled) - Molander, G. A.; Pack, S. K. (Tetrahedron, 2003)

(untitled) - Segal, I.; Zablotskaya, A.; Lukevics, E. (Chem. Heterocycl. Compd., 2005)

(untitled) - Shcheglova, N. M.; Kolesnik, V. D.; Ashirov, R. V. (Russ. J. Org. Chem., 2013)

(untitled) - Dorta, R.; Kelly, R. A., III; Nolan, S. P. (Adv. Synth. Catal., 2004)

(untitled) - Fürstner, A.; Guth, O.; Düffels, A.; Seidel, G.; Liebl, M.; Gabor, B.; Mynott, R. (Chem. – Eur. J., 2001)

(untitled) - Jimenez, L. R.; Tolentino, D. R.; Gallon, B. J.; Schrodi, Y. (Molecules, 2012)

(untitled) - Pump, E.; Slugovc, C.; Cavallo, L.; Poater, A. (Organometallics, 2015)

(untitled) - Musengimana, E.; Fatakanwa, C. (Orient. J. Chem., 2013)

(untitled) - Trnka, T. M.; Morgan, J. P.; Sanford, M. S.; Wilhelm, T. E.; Scholl, M.; Choi, T.-L.; Ding, S.; Day, M. W.; Grubbs, R. H. (J. Am. Chem. Soc., 2003)

(untitled) - Nyce, G. W.; Csihony, S.; Waymouth, R. M.; Hedrick, J. L. (Chem. – Eur. J., 2004)

US Patent - Bell, A.; Grubbs, R. H.; Morgan, J. P.; Moore, J. L. (High activity metal carbene metathesis catalysts generated using a thermally activated N-heterocyclic carbene precursor, 2001)

(untitled) - Arduengo, A. J., III; Calabrese, J. C.; Davidson, F.; Rasika Dias, H. V.; Goerlich, J. R.; Krafezyk, R.; Marshall, W. J.; Tamm, M.; Schmutzler, R. (Helv. Chim. Acta, 1999)

(untitled) - Tallarico, J. A.; Malnick, L. M.; Snapper, M. L. (J. Org. Chem., 1999)

(untitled) - Alcaide, B.; Almendros, P.; Luna, A. (Chem. Rev., 2009)